Methylated DNA impedimetric immunosensor based on azo-polymer-AuNPs dots and 5-methylcytosine antibody using dissolved oxygen as a redox probe - Olean-Oliveira, André [UNESP]; Monteiro Seraphim, Patricia [UNESP]; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2022)
The present work describes the development of an electrochemical immunosensor for the direct determination of methylated DNA using dissolved oxygen as the redox probe. The oxygen-sensitive response is possible due to the presence of a redox conducting polymer based on the Bismarck Brown Y dye (poly(azo-BBY)). In addition to the azo-polymer, gold nanoparticles (AuNPs) were formed in the polymer film by encapsulation to increase the active surface area and enhance sensor performance. The platform was easily synthesized using a single-step electropolymerization technique in a solution containing the BBY monomer and HAuCl4 salt. The immunosensor was developed by simply immobilizing the 5-methylcytosine antibody (Ab-5-mC) with high affinity to 5-mC on the surface of a device coated with azo-polymer-AuNPs dots. No secondary antibodies or enzymes were used in constructing this device. The immunosensor performance was evaluated by electrochemical impedance spectroscopy (EIS) in different concentrations of 5-methylcytosine (5-mC) in 0.10 mol L−1 phosphate buffer solution (PBS) solution containing atmospheric oxygen. A calibration curve was obtained by varying the resistance of the system as a function of the 5-mC concentration, revealing a limit of detection (LOD) in picograms per milliliter.
Keywords: Gold nanoparticle-polymer; Immunosensor; Methylated DNA sensor; Methylcytosine antibody; Secondary antibody less